Immunoproteomic identification and characterization of Ni2+-regulated proteins implicates Ni2+ in the induction of monocyte cell death - Jakob, Annika; Ohnesorge, Stefanie; Dietz, Lisa; Thierse, Hermann-Josef (Cell death & disease, 2017)
Nickel allergy is the most common cause of allergic reactions worldwide, with cutaneous and systemic effects potentially affecting multiple organs. Monocytes are precursors of not only macrophages but also dendritic cells, the most potent activators of nickel hypersensitivity. Monocytes are themselves important antigen-presenting cells, capable of nickel-specific T-cell activation in vivo and in vitro, in addition to being important for immediate innate immune inflammation. To elucidate early Ni2+-dependent inflammatory molecular mechanisms in human monocytes, a Ni2+-specific proteomic approach was applied. Quantitative two-dimensional (2D) differential gel electrophoresis and Delta2D software analyses coupled with matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) revealed that Ni2+ significantly regulated 56 protein species, of which 36 were analyzed by MALDI-MS. Bioinformatics analyses of all identified proteins resulted in Ni2+-associated functional annotation clusters, such as cell death, metal ion binding, and cytoskeletal remodeling. The involvement of Ni2+ in the induction of monocyte cell death, but not T-cell death, was observed at Ni2+ concentrations at or above 250 μM. Examination of caspase activity during Ni2+-mediated cell death revealed monocytic cell death independent of caspase-3 and -7 activity. However, confocal microscopy analysis demonstrated Ni2+-triggered cytoskeletal remodeling and nuclear condensation, characteristic of cellular apoptosis. Thus, Ni2+-specific peripheral blood mononuclear cell stimulation suggests monocytic cell death at Ni2+ concentrations at or above 250 μM, and monocytic effects on immune regulation at lower Ni2+ concentrations.